2021
DOI: 10.1002/er.6743
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective etherification of fructose and 5‐hydroxymethylfurfural over a novel Pd‐Ru/MXene catalyst for sustainable liquid fuel production

Abstract: Sustainable liquid fuel production from bio-oil compounds has attracted considerable attention in recent years. The catalytic etherification of 5-hydroxymethylfurfural (HMF) to ethoxymethylfurfural (EMF) is an effective approach for the production of liquid fuels. However, the development of high-performance and chemically stable catalysts has remained challenging.In this work, ultra-small Pd-Ru NPs were successfully immobilized on the surfaces of 2D MXene nanosheets (Pd-Ru/MXene) via fish sperm DNA-assisted m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The introduction of renewable diesel (RD) as fossil fuel replacement is attractive due to its similarity of chemical structure with petroleum diesel. RD is producible using biodiesel feedstocks such as microalgae, date seeds, Jatropha curcas and lignocellulosic biomass (Mofijur et al, 2013b;Bharath et al, 2021;Low et al, 2021;Oladipupo Kareem et al, 2021). However, the production often involves catalytic processes that are governed by catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of renewable diesel (RD) as fossil fuel replacement is attractive due to its similarity of chemical structure with petroleum diesel. RD is producible using biodiesel feedstocks such as microalgae, date seeds, Jatropha curcas and lignocellulosic biomass (Mofijur et al, 2013b;Bharath et al, 2021;Low et al, 2021;Oladipupo Kareem et al, 2021). However, the production often involves catalytic processes that are governed by catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding selected area electron diffraction (SAED) pattern of SnS 2 exhibits a polycrystalline structure and that of MXene is a single crystal. The concentric diffraction rings with radii from small to large correspond to lattice planes of (011), (001), (012), and (110) of hexagonal SnS 2 , and the bright spots correspond to a typical diffraction pattern for MXene . The elemental mapping information of MXene and MXene/SnS 2 heterojunctions are provided in the Supporting Materials.…”
Section: Resultsmentioning
confidence: 99%
“… Manjunathan et al, (2021 ) found a catalyst consisting of divinylbenzene (DVB) and sodium p-styrenesulfonate (SPSS) copolymerized with a sulfonated hydrophobic mesoporous organic polymer (MOP-SO 3 H) catalyst, which was able to achieve an EMF yield of 72.2% under the conditions of a bulk catalyst-catalyzed reaction. Bharath et al, (2021 ) immobilized the ultra-small Pd–Ru nanoparticles on the surface of 2D MXene nanosheets to produce a catalyst (Pd-Ru/MXene), which was reacted at 120°C for 2.5 h and was able to obtain a final EMF yield of 82%. Compared with the previous two catalysts, the catalyst prepared in this study has good catalytic effect.…”
Section: Resultsmentioning
confidence: 99%